2015
DOI: 10.1136/bcr-2015-211006
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia de Lange syndrome due to mosaic NIPBL mutation: antenatal presentation with sacrococcygeal teratoma

Abstract: A male infant at 36 weeks gestation was born by section. At 20 weeks of gestation, congenital diaphragmatic hernia and sacrococcygeal teratoma had been seen on ultrasound. At birth, the infant had features suggestive of Cornelia de Lange syndrome (CdLS). He remained hypoxic despite aggressive ventilatory manoeuvres and was palliated. At postmortem, the lungs were hypoplastic. In CdLS, mutations in NIPBL are found in around 50% of cases. Mutation analysis, including multiplex ligation dependent probe amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Sacrococcygeal teratomas are an especially common cause of NIHF, and reported genetic etiologies include MNX1 variants, partial monosomy 7q/trisomy 2p, and Cornelia de Lange syndrome . Other tumors occurring with NIHF include neuroblastomas, hemangiomas, fibrosarcomas, and rhabdomyosarcomas .…”
Section: Genetic Causes Of Nihf By Organ Systemmentioning
confidence: 99%
“…Sacrococcygeal teratomas are an especially common cause of NIHF, and reported genetic etiologies include MNX1 variants, partial monosomy 7q/trisomy 2p, and Cornelia de Lange syndrome . Other tumors occurring with NIHF include neuroblastomas, hemangiomas, fibrosarcomas, and rhabdomyosarcomas .…”
Section: Genetic Causes Of Nihf By Organ Systemmentioning
confidence: 99%
“…Little is known about the molecular features of SCT, and their pathogenesis remains unclear. Studies have predominantly shown normal karyotypes in pediatric SCTs [10,11], although a few cases have shown chromosomal abnormalities [12][13][14][15]. Expression of a subset of stem cells markers (NANOG, OCT4, SSEA-4 and nestin) has been found in SCT [9].…”
Section: Introductionmentioning
confidence: 99%